Exploring higher-order risk effects - Cary Deck; Harris Schlesinger (Center for Economic Studies and ifo Institute (CESifo), 2008)
Higher-order risk effects play an important role in examining economic behavior under uncertainty. A precautionary demand for saving has been linked to the property of prudence and the property of temperance has been used to show how the presence of an unavoidable risk affects one's behavior towards a second risk. These two properties also play key roles in aversion to negative skewness and to kurtosis, respectively. Both properties recently have been characterized by preferences over lottery pairs in simple 50-50 gambles. The simplicity of this characterization is ideal for experimental investigation. This paper reports the results of such experiments and concludes that there is behavioral evidence for prudence, but not for temperance. Implications of these results for both expected-utility and non-expected-utility models are examined.
Keywords: C9; D8; 330; Risk; prudence; temperance; laboratory experiments; Entscheidung bei Risiko; Entscheidung bei Unsicherheit; Verhaltensökonomik; Test; Sparen